Stock structure of the English Channel common cuttlefish Sepia officinalis (Linnaeus, 1758) during the reproduction period. (28th July 2015) - Gras, Michaël; Safi, Georges; Lebredonchel, Hugo; Quinquis, Jérôme; Foucher, Éric; Koueta, Noussithé; Robin, Jean-Paul
Abstract : Within the English Channel, the common cuttlefish Sepia officinalis is a semelparous species for which a 2-year life cycle was exclusively described in the 1980s. In the 1990s, new research indicated that whilst a 2-year life cycle was still evident for females and the large majority of males, a small proportion of males were actually maturing at only 1 year of age. Since 1980, the interest of French and UK fishers for this resource has increased and it is nowadays one of the most important demersal species of the area and is considered to be fully exploited. From the start of the 20th century, fishing effort and sea surface temperatures have increased in the English Channel and have probably impacted the life history traits of S. officinalis . A 2-year sampling programme was undertaken at French landing sites of the English Channel during the reproduction season in 2010 and 2011 to estimate if the proportion of 1-year-old mature animals has changed. Age determination was carried out by coupling polymodal decomposition and lipofuscin measurement. Size-at-maturity for each year and each sex was estimated by fitting a binomial error GLM. Results highlight that a variable percentage of males and females belonging to the first cohort are mature and that size-at-maturity was lower than that observed in the 1990s. Finally, different parameters, such as temperature and fishing pressure are explored to discuss changes in life history traits suggesting that cuttlefish could be an indicator of the temperature regime shift in the English Channel.